The impact of the development of society on economic and financial crime: Case study for European Union member states - Monica Violeta Achim; Viorela Ligia Vaidean; Sorin Nicolae Borlea; Decabal Remus Florescu (Risks, 2021)
Economic and financial crime is closely related to the changes and the development of societies. In this paper, we question whether the types of economic and financial crimes change as the society develops or not. For our purpose, we use the sample of 27 European Union member countries, for the 2005-2020 time period, which forms an unbalanced panel dataset. The main econometric method is represented by the Pooled OLS method for panel data. Our findings highlight that higher economic and sustainable development determines a reduction in the levels of corruption, shadow economy, and cybercrime. Additionally, we find that increased economic and sustainable development is related to higher levels of money laundering. These findings help governments to understand the way in which various types of economic and financial crimes unfold within different contexts of economic development, in order to implement specific policies for reducing the general level of crimes.
Keywords: 330; corruption; shadow economy; money laundering; cybercrime; economic development; sustainable development